Cur@ZIF-8@BA nanomaterials with pH-responsive and photodynamic therapy properties promotes antimicrobial activity - Shang, Xiujuan; Wang, Hongdong; Yu, Yongbo; Gu, Jin; Zeng, Jian; Hou, Sinan (Frontiers in Chemistry, 2024)
Antimicrobial photodynamic therapy (aPDT) has emerged as a highly promising strategy for non-antibiotic treatment of infections due to its unique advantages in efficient bactericidal action and reduction of drug resistance. The natural photosensitizing properties of curcumin (Cur) are widely acknowledged; however, its limited bioavailability has impeded its practical application. In this study, we developed a nanomaterial called Cur@ZIF-8@BA by encapsulating Cur within ZIF-8 and modifying the surface with boric acid (BA). The Cur@ZIF-8@BA exhibits pH-responsive properties and enhances bacterial binding, thereby effectively promoting photodynamic therapy. Moreover, its antibacterial activity against E. coli, Staphylococcus aureus and A. baumannii is significantly increased in the presence of light compared to a dark environment. The mechanism behind this may be that BA increases the affinity of Cur@ZIF-8@BA towards bacteria, and making released Zn2+ and BA from the nanomaterial increase bacterial cell membrane permeability. This facilitates efficient delivery of Cur into bacterial cells, resulting in generation of abundant reactive oxygen species (ROS) and subsequent bactericidal activity. In conclusion, our prepared Cur@ZIF-8@BA holds great promise as a photodynamically mediated antimicrobial strategy.